Does Nepal's Financial Structure Matter for Economic Growth? - Kharel, Ram Sharan; Pokhrel, Dilli Ram (NRB Economic Review, 2012)
Despite causality debate, a number of empirical literatures (Pagano, 1993 and Levine, 1997, among others) suggest a positive relationship between financial sector development and economic growth. Moreover, there remains further debate whether the country's financial structure exerts differential impact on economic growth. Empirical studies across the countries (Rajan and Zingales, 1999 and Arestis et. al. 2004) suggest that banking sector plays a key role in some countries while the capital market has a lead position in others for enhancing economic growth. In this context, this paper investigates the relative merits of banking sector vs. capital market in promoting economic growth in Nepal. The empirical results using Johansen's cointegrating vector error correction model based on aggregate annual data from 1993/9 to 2010/11 suggest that banking sector plays a key role in promoting economic growth compared to capital market in Nepal. It may be either the size of capital market is too small to seek the relationship or it is weakly linked to real economic activities. Our result implies that the policy should focus on banking sector development by enhancing its quality and outreach as it promotes economic growth in Nepal.